Clinical aspects of diarrhea during the pandemia of COVID-19 - Z. A. Khokhlova; R. A. Gileva; T. V. Sereda; N. M. Zhilina; A. A. Keller; V. N. Karpova (Журнал инфектологии, 2022)
The aim. To investigate the clinical peculiarities of adult patients with diarrheal syndrome, associated with coronavirus infection COVID-19.The materials and methods. There has been carried out the analysis of 56 patients aged 26-81 years, hospitalized with acute enteric infection at the Municipal Infectious Diseases Hospital №8 (not reprofiled as hospital for the treatment of coronavirus infection COVID-19 patients) in the course of August 2020 – February 2021 and the patients with cause-effect relationship with COVID-19. There have been used the routine diagnostic methods, the analysis of feces for causative agents of diarrhea was tested by the methods of bacteriological and immunoenzymatic analysis, the analysis of feces for toxins A and B Clostridium difficile was tested method of immunochromatographic assay; the blood serum was tested by method of immunoenzymatic analysis and the analysis of nasopharyngeal swabs was tested by immunochromatographic assay and PCR test for markers SARS-COV-2. The statistical material treatment has been done using Statistical Package of IBM SPSS Statistics-22.The results. There have been registered 51,8% of cases – diarrhea as one of the clinical manifestations of COVID-19 in adult patients (the first group of patients), in 48,2% of cases – diarrhea as a result of recently treated COVID-19 and a massive course of antibiotics (the second group of patients). In the second group 12 patients have been diagnosed with clostridial infection, 15 patients – with antibiotic-associated diarrhea. There has been registered the main severity of clinical manifestations in patients with clostridial infection. The disease being characterized by severity of colitis syndrome, the blood sedimentation rate increasing, hyperleukocytosis in haemogram, hypoproteinemia and hypoalbuminemia. The aggravating factors are combined comorbidity and patients aged over 55 years.The conclusion. There should be used the differential approach for diarrheal syndrome in patients with coronavirus infection. Taking into account the massive course antibiotics’ side effects, the analysis of feces for pathogenic flora must be included into the medical examinations such as Clostridium difficile and the course of probiotic and anticlostridial medicines should be done.